Dasar Pertimbangan Hakim Dalam Penjatuhan Pidana Terhadap Anak Sebagai Pelaku Membujuk Dan Melakukan Persetubuhan (Studi Kasus Putusan Nomor 00/PID.SUS-Anak/2022/PTBBL) - Aramadanna; Rahayu, Sri; Toni (Shofanah Media Berkah, 2024)
Base the judge's consideration of Decision Number 00/PID.SUS-ANAK/2022/PT BBL in sentencing the perpetrator is a crime less than half the criminal threat , the judge considers in imposing a crime against child as perpetrator arranged based on legal considerations​ nor nonjuridical contains facts juridical matters in trials, such as the public prosecutor's indictment, public prosecutor's demands, witness statements, defendant's statements and evidence or evidence currently in a way nonjuridical seen from How background behind defendant And consequence from deed defendant. The aim of this research is to find out the basis of the judge's considerations in sentencing children as perpetrators of persuading and committing sexual intercourse and to find out the factors that influence the judge's considerations in sentencing children as perpetrators of persuading and committing sexual intercourse. The method used is normative juridical with a case approach. Result of study This base judge 's consideration dropping criminal in a way juridical that the judge's decision is considered contrary to the Principle of Legality And in a way nonjuridical consequence from deed perpetrator give rise to trauma to the victim, even loss to the victim. Factors who influence according to law enforcers in the decision 00/PID.SUS-Anak/2022/PT BBL do not agree if The crime is imposed entirely on the child. So it is not appropriate if the punishment does not achieve a sense of justice Law enforcers should stick to decisions taken on the basis of professional reasoning and calculations.